Measurement of CP violation in the decay B+→K+π0 - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2021)
A measurement of CP violation in the decay B+→K+π0 is reported using data corresponding to an integrated luminosity of 5.4 fb−1 collected with the LHCb experiment at a center-of-mass energy of √s=13 TeV. The CP asymmetry is measured to be 0.025±0.015±0.006±0.003, where the uncertainties are statistical, systematic, and due to an external input. This is the most precise measurement of this quantity. It confirms and significantly enhances the observed anomalous difference between the direct CP asymmetries of the B0→K+π− and B+→K+π0 decays, known as the Kπ puzzle.
Im Titel sind "+" und "0" hochgestellt
Gesehen am 13.04.2021